Consumers' Preferences Toward Organic Tomatoes: A Combined Two-Phase Revealed-Stated Approach. Issue 1 (2nd January 2016) - Becker, Nir; Tavor, Tchai; Friedler, Lili; Bar (Kutiel), Pua
ABSTRACT: We analyzed consumers of organic and nonorganic tomatoes in Israel with respect to their sociodemographic characteristics and their attitudes regarding organic food consumption. More specifically, we were interested in the public motives (environmental attitudes) vs. private motives (health). Since environmental motives dictate a binary decision, while health motives can be accommodated with a range of intermediate decisions, consumers in our model could choose to be either organic or nonorganic consumers, as well as choose how many tomatoes they consume. The decision was rested with repeated price premiums for organic tomatoes. Results reveal that price was not an important component in the decision to be or not to be an organic tomato consumer. However, price premium was important when considering the amount of tomatoes to consume. Thus, our study does not confirm the results of other studies that point to the sole motive of health benefits for buying organic food.